2021
DOI: 10.1002/aelm.202100496
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Conductive Cellulose Composite Paper for Highly Efficient Electromagnetic Interference Shielding

Abstract: Developing highly efficient electromagnetic interference (EMI) shielding materials with outstanding mechanical properties are urgently desirable for portable device hardware and flexible electronic devices. Herein, a highly conductive and flexible silver nanowires/graphene nanosheets/cellulose (AgNWs/GNSs/cellulose) composite paper with particular three‐layered structures is fabricated via vacuum assisted filtered and coating method. The prepared composites exhibit excellent EMI shielding property due to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…These phenomena were also observed in other various shielding materials such as carbon nanotubes and Mxene. 6,59,60 In addition, as shown in Figure S8c, the interior of the Ag NMs/ePLLA conductor with multiple layers induced multiple reflections that could not be ignored and consumed large amounts of electromagnetic waves. Besides the EMI shielding effectiveness, the EMI shielding materials also require a light weight and thin thickness for special applications such as wearable electronics and military and aerospace purporses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These phenomena were also observed in other various shielding materials such as carbon nanotubes and Mxene. 6,59,60 In addition, as shown in Figure S8c, the interior of the Ag NMs/ePLLA conductor with multiple layers induced multiple reflections that could not be ignored and consumed large amounts of electromagnetic waves. Besides the EMI shielding effectiveness, the EMI shielding materials also require a light weight and thin thickness for special applications such as wearable electronics and military and aerospace purporses.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33 Compared with reported cellulose-based EMI shielding materials (Fig. 5e and Table S4 †), [34][35][36][37][38][39] CCNB 4 -10 This journal is © The Royal Society of Chemistry 2022 achieved excellent mechanical properties, electrical conductivity, and EMI-shielding efficiency, thereby revealing the feasibility of using CCNBs for high-performance EMI-shielding materials.…”
Section: Applications Of Ccnbsmentioning
confidence: 90%
“…19 Hence, green paper based EMI shielding materials with the advantages of low cost, renewability, and biodegradability have attracted widespread attention. [20][21][22][23] For example, Zhang et al 22 reported a three-layer structured highly conductive flexible silver nanowire/graphene nanosheet/cellulose composite paper via the vacuum-assisted filtration and coating method, exhibiting an EMI shielding effectiveness (SE) of 53.3 dB at a thickness of only 0.17 mm. In addition, Li et al 20 prepared a biodegradable paper based material composed of an electromagnetic loss layer (graphene/nanosilver coating) and a reflective layer (aluminum film layer), and an ultra-high EMI SE of 92.29 dB within 8-13 GHz was successfully achieved.…”
Section: Introductionmentioning
confidence: 99%